DEPRESSÃO PÓS-PARTO: GRAVIDADE DOS SINTOMAS E ALIANÇA TERAPÊUTICA - Osório, Camila Moreira (2006)
Puerpério, Características do paciente, Relação terapêutica. 21 ABSTRACT Objective: to assess the impact of symptom severity on the development of the therapeutic alliance in women with postpartum depression undergoing brief cognitive psychotherapy. Method: this study is part of a randomised controlled trial that investigated the effectiveness of psychotherapy in the treatment of postpartum depression. Women were between 30 and 60 days postpartum and had a positive screen for mild to moderate depression. To assess depressive symptom severity, the Beck Depression Inventory was employed at the beginning and at the completion of treatment. The client and therapist forms of the Working Alliance Inventory (WAI) were used to evaluate the therapeutic alliance after the session 1, 4, 7. Data was analyzed with correlations and chi-square tests. Results: correlation analysis pointed to associations of the total WAI score (r = -0,35) and subscale task (r = -0,31) and bond (r = -0,57). Chi-squares tests were significant in the fourth session for the total WAI score (p ≤ 0,050) and the bond subscale (p. ≤ 0,037). Conclusion: the association of the investigated variables during the intermediary phase of the treatment was insufficient to indicate that depressive symptom severity had influence on the development of the therapeutic alliance.